Protective Effect of Aqueous Crude Extract of Neem (Azadirachta indica) Leaves on Plasmodium berghei-Induced Renal Damage in Mice - Voravuth Somsak; Sukanya Chachiyo; Ubonwan Jaihan; Somrudee Nakinchat (Journal of Tropical Medicine)
Malaria is a major public health problem in the world because it can cause of death in patients. Malaria-associated renal injury is associated with 45% of mortality in adult patients hospitalized with severe form of the disease. Therefore, new plant extracts to protect against renal injury induced by malaria infection are urgently needed. In this study, we investigated the protective effect of aqueous crude extract of Azadirachta indica (neem) leaves on renal injury induced by Plasmodium berghei ANKA infection in mice. ICR mice were injected intraperitoneally with 1 × 107 parasitized erythrocytes of PbANKA, and neem extracts (500, 1,000, and 2,000 mg/kg) were given orally for 4 consecutive days. Plasma blood urea nitrogen (BUN) and creatinine levels were subsequently measured. Malaria-induced renal injury was evidenced as marked increases of BUN and creatinine levels. However, the oral administration of neem leaf extract to PbANKA infected mice for 4 days brought back BUN and creatinine levels to near normalcy, and the highest activity was observed at doses of 1,000 and 2,000 mg/kg. Additionally, no toxic effects were found in normal mice treated with this extract. Hence, neem leaf extract can be considered a potential candidate for protection against renal injury induced by malaria.